To find the height \( h \) of the square pyramid, we need to first determine the radius \( r \) of the base of the pyramid. Since the base of the pyramid is a square, the radius \( r \) can be defined as half of the side length of the base.
-
Finding the Length of the Base Edge:
Let's denote the length of the base edge as \( a \). Since the base is square, we know: \[ r = \frac{a}{2} \]
-
Using the Pythagorean Theorem:
In the right triangle formed by the height \( h \), the radius \( r \), and the slant height \( s \), we apply the Pythagorean theorem: \[ s^2 = h^2 + r^2 \]
We know:
- The slant height \( s = 24 \) in,
- The lateral edge length \( e = 25 \) in.
-
Finding the Height:
Since \( e \) is the hypotenuse of another right triangle formed with \( h \) and \( r \), we can use: \[ e^2 = h^2 + r^2 \]
We'll solve these equations step by step. First, express \( r \) in terms of \( e \) and \( h \): \[ 25^2 = h^2 + r^2 \] \[ 625 = h^2 + r^2 \] (1)
And we already have: \[ 24^2 = h^2 + r^2 \] \[ 576 = h^2 + r^2 \] (2)
-
Setting Up the Equations:
Now we can set the equations (1) and (2) together:
- From equation (2), we isolate \( r^2 \): \[ r^2 = 576 - h^2 \]
Substitute \( r^2 \) from equation (2) into equation (1): \[ 625 = h^2 + (576 - h^2) \] \[ 625 = 576 \]
-
Solving for \( h \): Now, we can subtract \( 576 \) from both sides to find \( h^2 \): \[ 625 - 576 = h^2 \] \[ 49 = h^2 \] \[ h = \sqrt{49} = 7 \] in.
So, the height of the pyramid \( h \) is 7 inches.